A Comparative Analysis of Multi-criteria Decision Models for ERP Package Selection for Improving Supply Chain Performance. (September 2016) - Ghosh, Indranil; Biswas, Sanjib
Advancement in information and communication technology (ICT) has turned information as one of the key organisational resources for managing business operations. In this information age, one of the key strategic considerations for achieving competitive advantage involves an information intensive supply chain management (SCM), integrating all the activities and partners beyond the enterprise boundaries. Enterprise resource planning (ERP) forms the backbone of such extended enterprises. There has been a growing interest of the organisations to invest in the ERP solutions. However, selection of an appropriate ERP package plays a critical role in achieving the business objectives. In this article, we have identified the criteria for selecting an appropriate ERP package. Further, we have used different multi-criteria decision analysis (MCDA) methods for ranking of the alternative ERP packages to select a suitable one. A comparative analysis has been carried out. Some future scopes of work have also been highlighted.